2020
DOI: 10.29060/taps.2020-5-3/oa2166
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported perception of a Dedicated research semester in Pharmacy curriculum in enhancing research competencies

Abstract: This study measures the impact of the implementation of a dedicated research semester on various perceived competencies related to research. In 2016, surveys were conducted on final undergraduate Pharmacy students in regard to appraisal and critical thinking skills. Students’ perceptions of the impact of research in enhancing their employment potential were investigated. Our evaluation included students’ self-assessment of their writing, presentation, critical thinking and research skills. To assess qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This study could demonstrate the roles of assessment rubrics in helping students perceive expectations about their attitudes and research performance and in facilitating supervisors' evaluation and feedback processes. Although the research project module could provide undergraduate pharmacy students with an excellent and helpful experience to develop specific research skills and enhance their competencies and selfassurance in undertaking research work, students struggled with several challenges in their initial research exposure (Tan et al, 2020). Assessment rubrics prepare students for research by providing a broad understanding of the expectations for their attitudes, research conduct, and data collection, analysis, and interpretation, while allowing for a clear and transparent evaluation of their research performance (Jonsson, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study could demonstrate the roles of assessment rubrics in helping students perceive expectations about their attitudes and research performance and in facilitating supervisors' evaluation and feedback processes. Although the research project module could provide undergraduate pharmacy students with an excellent and helpful experience to develop specific research skills and enhance their competencies and selfassurance in undertaking research work, students struggled with several challenges in their initial research exposure (Tan et al, 2020). Assessment rubrics prepare students for research by providing a broad understanding of the expectations for their attitudes, research conduct, and data collection, analysis, and interpretation, while allowing for a clear and transparent evaluation of their research performance (Jonsson, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Research exposure has been reported to enrich the learning experience of undergraduate students of various programmes, including pharmacy (Tan, 2007;Lee et al, 2010;Laidlaw et al, 2012;Harirforoosh & Stewart, 2016;Bhagavathula et al, 2017). The research experience enhances students' understanding of research and allows them to discover their research interests where they can further pursue graduate studies and, subsequently, a career as a researcher (Lopatto, 2007;Murdoch-Eaton et al, 2010;Tan et al, 2020). Indeed, scholarly activities might raise students' interest in pursuing academic pharmacy as their profession (Nykamp et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation